2018
DOI: 10.1016/j.ccell.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the HTLV-I-Regulated BATF3/IRF4 Transcriptional Network in Adult T Cell Leukemia/Lymphoma

Abstract: Adult T cell leukemia/lymphoma (ATLL) is a frequently incurable disease associated with the human lymphotropic virus type I (HTLV-I). RNAi screening of ATLL lines revealed that their proliferation depends on BATF3 and IRF4, which cooperatively drive ATLL-specific gene expression. HBZ, the only HTLV-I encoded transcription factor that is expressed in all ATLL cases, binds to an ATLL-specific BATF3 super-enhancer and thereby regulates the expression of BATF3 and its downstream targets, including MYC. Inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(128 citation statements)
references
References 39 publications
7
120
1
Order By: Relevance
“…A recent study has shown that HBZ transactivates the basic leucine zipper ATF-like transcription factor 3, which forms a transcriptional complex with another transcription factor, interferon response factor 4 (IRF4), to promote ATL cell gene expression and proliferation. 27 Remarkably, the ablation of HBZ via CRISPR-Cas9 reduced the viability of ATL cells. 27 It is unclear whether the loss of cell viability is due to the senescence response associated with NF-kB hyperactivation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study has shown that HBZ transactivates the basic leucine zipper ATF-like transcription factor 3, which forms a transcriptional complex with another transcription factor, interferon response factor 4 (IRF4), to promote ATL cell gene expression and proliferation. 27 Remarkably, the ablation of HBZ via CRISPR-Cas9 reduced the viability of ATL cells. 27 It is unclear whether the loss of cell viability is due to the senescence response associated with NF-kB hyperactivation.…”
Section: Discussionmentioning
confidence: 99%
“…27 Remarkably, the ablation of HBZ via CRISPR-Cas9 reduced the viability of ATL cells. 27 It is unclear whether the loss of cell viability is due to the senescence response associated with NF-kB hyperactivation. Importantly, IRF4 gene amplification and gain-of-function mutations frequently occur in ATL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBZ and HTLV-I-encoded TFs integrate into ATLL-specific BATF3 SE, further enhancing MYC expression by linking with BATF3/IRF4. Overexpressed MYC exacerbates disease through MYC seRNA transcription [68]. Interestingly, the nuclear matrix protein SAFA (also known as HNRNPU) displays an antiviral function by promoting immunity and stimulating productions of SE and seRNA of antiviral genes, including type I IFNs [69].…”
Section: Oncogenic Serna Formationmentioning
confidence: 99%
“…UBE4B knockdown significantly impaired the expression of CD25 in Tax+ MT-2, HUT-102 and C8166 cell lines, but not in Tax-TL-OM1 cells ( Figure 4B, C). Expression of IRF-4, a transcription factor critical for the survival of ATLL cell lines [43], was significantly decreased in MT-2, but not in HUT-102, C8166 or TL-OM1 cells upon UBE4B depletion ( Figure 4B, C). Expression of cIAP-2, an anti-apoptotic NF-κB target gene, was significantly decreased in HUT-102, but not in MT-2, C8166 or TL-OM1 cells when UBE4B was knocked down ( Figure 4B).…”
Section: Knockdown Of Ube4b Impairs Tax-induced Expression Of Nf-κb Tmentioning
confidence: 99%